1994
DOI: 10.1021/bi00175a031
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin Inhibits the Glutaraldehyde-Induced Cross-Link between the Central 48-kDa Fragment of Myosin Head and Segment 48-67 in Actin Subdomain 2

Abstract: The glutaraldehyde-induced cross-linking of the F-actin-myosin head (S1) complex, previously described [Bertrand et al. (1988) Biochemistry 27, 5728-5736], was investigated in the presence of tropomyosin (Tm) alone or associated with troponin (Tn), at a Tm-Tn/actin/S1 molar ratio of 1:7:3. Among the two acto-S1 cross-linked products with apparent masses of 165 and 200 kDa generated in the absence of the regulatory proteins, only the 165-kDa adduct was formed in the presence of Tm. An identical result was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 85 publications
1
20
0
Order By: Relevance
“…However, Squire and Morris (12) raised the possibility that changes seen in the structural studies of regulated thin filaments may be due not only to shifts of the Tm/Tn complex, but also to subdomain 2 movements within each actin protomer. The observations that selected subdomain 2 alterations impair regulation by troponin-tropomyosin (13,14) and that the presence of Tm and Tm/Tn interferes with cross-linking between subdomain 2 and S1 (15) are consistent with this hypothesis. Moreover, the recent paper of Luo et al (16), reporting the cross-linking of Tn-I to Met 47 on subdomain 2 of actin, suggests that TnI interacts with this region of actin.…”
supporting
confidence: 64%
“…However, Squire and Morris (12) raised the possibility that changes seen in the structural studies of regulated thin filaments may be due not only to shifts of the Tm/Tn complex, but also to subdomain 2 movements within each actin protomer. The observations that selected subdomain 2 alterations impair regulation by troponin-tropomyosin (13,14) and that the presence of Tm and Tm/Tn interferes with cross-linking between subdomain 2 and S1 (15) are consistent with this hypothesis. Moreover, the recent paper of Luo et al (16), reporting the cross-linking of Tn-I to Met 47 on subdomain 2 of actin, suggests that TnI interacts with this region of actin.…”
supporting
confidence: 64%
“…2 B and D) could supplant the originally proposed secondary binding site. There are (tropomyosin-dependent) cross-linking data supporting this suggestion (29). Actin residue 43, which is always hydrophobic (30), may interact with S1 residue 554 (Ͼ97% hydrophobic).…”
Section: Discussionmentioning
confidence: 88%
“…in the absence of Ca 2ϩ ) indicate that tropomyosin may bridge over subdomain 2 without extensive contact (4 (17)(18)(19)(20). Actin mutants provide an alternative approach to assess specific interactions between tropomyosin and actin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a Drosophila melanogaster actin subdomain 2 mutant, E93K, which inhibits tropomyosin-actin sliding in isolated protein preparations, has been utilized to investigate tropomyosin-based regulation (16). These and other data (17)(18)(19)(20) suggested that actin subdomain 2 may be important for tropomyosin and troponin function. Recently, we have shown that Saccharomyces cerevisiae actin can serve as a model system for examining troponin-tropomyosin-mediated regulation (21).…”
mentioning
confidence: 99%